2016
DOI: 10.1093/aob/mcw184
|View full text |Cite
|
Sign up to set email alerts
|

Temperate rain forest species partition fine-scale gradients in light availability based on their leaf mass per area (LMA)

Abstract: Background and Aims Ecologists are increasingly using plant functional traits to predict community assembly, but few studies have linked functional traits to species' responses to fine-scale resource gradients. In this study, it was tested whether saplings of woody species partition fine-scale gradients in light availability based on their leaf mass per area (LMA) in three temperate rain forests and one Mediterranean forest in southern Chile.Methods LMA was measured under field conditions of all woody species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
16
1
Order By: Relevance
“…This pattern, which is contrary to what is commonly found at the interspecific level in tropical and northern hemisphere temperate forests (Walters and Reich , Poorter et al. ), was also found across species in the temperate rainforest of southern Chile (Fajardo and Siefert ).…”
Section: Discussioncontrasting
confidence: 96%
“…This pattern, which is contrary to what is commonly found at the interspecific level in tropical and northern hemisphere temperate forests (Walters and Reich , Poorter et al. ), was also found across species in the temperate rainforest of southern Chile (Fajardo and Siefert ).…”
Section: Discussioncontrasting
confidence: 96%
“…Specifically, species that occurred across a wide range of light environments had high ITV in leaf N concentration, and species broadly distributed along the soil P availability gradient had high ITV in leaf N and P. Importantly, we found these positive relationships between niche breadth and ITV by comparing species’ ITV measured across a common set of environments. Research conducted in these southern hemisphere cool temperate rainforests thus far (Lusk , Fajardo and Siefert , Peltzer and Wardle ) has commonly focused on light availability as the limiting factor, especially, for regeneration, but here we show that soil N and P availability had a strong positive relationship with leaf trait variation, indicating that multiple environmental filters drive regeneration dynamics (see also Lusk and Laughlin , Fajardo and Siefert ). Although some studies have found that N is the most limiting nutrient in soils of temperate rainforests in southern Chile (Huygens et al ), the volcanic origin of these soils makes them very poor in available P for plants (large amount of allophane and sesquioxide in the soil, which have a high phosphate‐fixing capacity, making P not readily available for plants) (Fajardo and Piper ).…”
Section: Discussionmentioning
confidence: 49%
“…In temperate rainforests of southern Chile, where as many as 25 woody species per hectare can co‐occur within forest communities, species can be found in a variety of local environmental conditions, from deep shade to tree‐fall canopy gaps (Veblen 1985, Lusk , Fajardo and Siefert , ), and from spots with poor to rich nutrient availability. Given these apparent strong environmental gradients, we expected that species achieving high local abundance would be those that could tolerate a wide range of environments by adjusting their trait values to local conditions (Darwin 1859, Sides et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations